2011
DOI: 10.1152/ajpcell.00405.2010
|View full text |Cite
|
Sign up to set email alerts
|

The calcium channel α21 subunit interacts with ATP5b in the plasma membrane of developing muscle cells

Abstract: García J. The calcium channel ␣2/␦1 subunit interacts with ATP5b in the plasma membrane of developing muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Thus, the fold increase in the levels of α 1, β , and γ were substantially higher than for α 2 δ 1. Overall the mRNA data demonstrate that α 2 δ 1 is expressed earlier than α 1 and at higher levels than β or γ subunits in satellite cells and are consistent with studies detecting different protein levels of a2 δ 1 and α 1 subunits early in development [9, 17]. …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the fold increase in the levels of α 1, β , and γ were substantially higher than for α 2 δ 1. Overall the mRNA data demonstrate that α 2 δ 1 is expressed earlier than α 1 and at higher levels than β or γ subunits in satellite cells and are consistent with studies detecting different protein levels of a2 δ 1 and α 1 subunits early in development [9, 17]. …”
Section: Resultssupporting
confidence: 88%
“…The β subunit is an intracellular protein involved in the regulation of gene expression in different cell types including myoblasts [57]. The α 2 δ 1 protein is an extracellular protein involved in cell attachment and migration and possibly cell signaling in myoblasts [8, 9]. We recently found that the α 2 δ 1 subunit localizes at the leading ends of myotubes with little or no association with α 1 subunits 2 days after the induction of differentiation [8] suggesting that, in addition to attachment and migration, α 2 δ 1 may play a role in the elongation process of myotubes.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of normal calcium currents in the BDNF mutant VMH suggests that anorexigenic effects of BDNF and ␣2␦-1 in this region are unlikely to be calcium channel dependent. Interestingly, effects of ␣2␦-1 unrelated to its role as a calcium channel subunit have been described in myotubes, where it is localized separately from calcium channel complexes (García, 2011). Knockdown of ␣2␦-1 in these cells impaired several cellular functions, including migration and attachment without affecting calcium currents (García et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, effects of ␣2␦-1 unrelated to its role as a calcium channel subunit have been described in myotubes, where it is localized separately from calcium channel complexes (García, 2011). Knockdown of ␣2␦-1 in these cells impaired several cellular functions, including migration and attachment without affecting calcium currents (García et al, 2008). Directly relevant to our findings, ␣2␦-1 also interacts with TSPs to facilitate excitatory, but not inhibitory, synapse assembly in retinal ganglion and cortical neurons (Eroglu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ATP synthase subunit beta has been linked to Bcl-xl which is involved in apoptosis regulation (135). Subunit beta is also involved in calcium signalling at the plasma and intracellular membranes of developing muscle cells (136). As the main cytotoxic component of HAMLET is the oleic acid rather than the protein, the binding of HAMLET protein to ATP synthase protein subunits is likely a result of the unfolded HAMLET protein, no longer partially folded around its oleic acid cargo, binding to the ATP synthase subunits that are in proximity to HAMLET and are themselves now dissociated.…”
Section: Binding To Nucleotide-binding Proteinsmentioning
confidence: 99%